Utilization of E-Campus in Supporting Arabic Language Learning for the Interests of Four Skills in College Students - Amrina, Amrina; Umainah, Fita (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
The problems experienced by students in the Arabic language learning process are lacking in understanding the learning. This is due to the lack of innovation in learning in college and also due to the lack of learning media used to support the learning process in college. The purpose of this study was to support Arabic language learning using the e-campus learning system in college. The method used by the researcher is the quantitative method, which method can show that this research is in the form of data containing numbers. The data was obtained using the Google from application as a means to create a questionnaire containing questions which were then distributed to respondents who were used as the results of the research subjects. The results of the study showed that there was the use of e-campus in supporting Arabic language learning for students in college. The conclusion of this study explains that the e-campus application can be used in Arabic language learning which can increase students' enthusiasm for learning and can also test and determine their ability to understand Arabic language learning in college. The limitations of this study are that the researcher only conducted research on the e-campus application as a medium for learning Arabic in college. This study also recommends that further researchers conduct research using e-campus as a medium for learning Arabic, but it should be further developed to become a challenge in using e-campus in learning Arabic.